O cotidiano de pessoas em uso problemático de álcool e outras drogas e a terapia ocupacional - Faria, Paula de Fátima Oliveira (Universidade Federal de São Carlos, 2021)
As it is a cross-cutting theme in several areas such as health, justice, education, social assistance and development, the problematic use of alcohol and other drugs requires an understanding of the factors that make up the daily lives of people who do such use. The concept of daily life is understood as a key-concept that refers to the production of knowledge and practices in occupational therapy, and is linked to the research theme that we proposed to investigate. The research was developed through two complementary studies, Study 1 aimed to investigate the role of occupational therapists with people in psychological distress resulting from the use of alcohol and other drugs, focusing on daily life. Study 2 had as general objective to understand the daily life of people in psychological distress resulting from the use of alcohol and other drugs linked to a CAPS AD (Alcohol and Drugs Psychosocial Care Center), from their perspective. Study 1 was based on the investigation of the performance of occupational therapists in the state of São Paulo, CAPS AD workers, focusing on the daily lives of people who make problematic use of alcohol and other drugs. Study 2 was based on contact with people who make problematic use of alcohol and other drugs linked to a CAPS AD in the interior of the state of São Paulo, through participant observation. Data collection for Study 1 was based on a semi-structured questionnaire sent by email with the Google Forms link. For data collection from Study 2, field diary records and complementary open interviews were used. Twelve occupational therapists working at CAPS AD in the state of São Paulo participated in Study 1, and in Study 2, six people with problematic use of alcohol and other drugs. The data produced were analyzed using thematic analysis, and for the analysis of Study 2 we anchored in the perspective of Agnes Heller's Theory of Everyday Life.The results of Study 1 pointed to five categories of analysis: Concept of Daily Life; Territory conception and performance in the perspective of daily life; Daily Activities and Occupations; The Centrality of Alcohol and Other Drugs in Daily Life and Stigma. The vast majority of occupational therapists reported that understanding, problematizing and expanding the daily life of people in psychological distress due to the problematic use of alcohol and other drugs is an ethical-political challenge, making it necessary to identify the immediacy of the AD clinic and expand care beyond the survival of these people through the rescue of life history, affections, desire and creation. The results of Study 2 revealed that people with problematic use of alcohol and other drugs perceive themselves as stigmatized, link the use to the context of violence, experienced mainly in family relationships, as well as the lack of guarantee of basic rights in childhood is directly related to living on the street. They refer that the context of gender and police violence mark their daily lives. The reports registered that the CAPS AD works in the daily life of this population, guaranteeing rights and encouraging protagonism and, finally, they showed the means found for survival on the street, in relation to basic rights such as housing, food, among others. We hope that this research can help to understand the daily lives of people in psychological distress resulting from the problematic use of alcohol and other drugs and contribute to directing Occupational Therapy actions focusing on the daily lives of this population.
The everday life of people in problematic use of alcohol and drugs
Keywords: Terapia ocupacional; Cotidiano; Centro de atenção psicossocial; Usuários de drogas; Occupational therapy; Everyday life; Psychosocial care center; Drug user; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL